Biogeochemical Dynamics in a Eutrophic Tidal Estuary Revealed by Isotopic Compositions of Multiple Nitrogen Species. Issue 7 (6th July 2019) - Yan, Xiuli; Wan, Xianhui Sean; Liu, Li; Xu, Min Nina; Tan, Ehui; Zheng, Zhenzhen; Zou, Wenbin; Tian, Li; Li, Da‐Wei; Trull, Thomas W.; Kao, Shuh‐Ji
Abstract: Estuaries sit at the land‐ocean boundary and act as natural reactors for nitrogen (N) transformations among numerous forms. Superimposing onto physical mixing, biological processes lead to nonconservative N behavior in estuaries. Under the coinfluences of biological alteration and multiple end‐members, however, some N species can exhibit apparent conservation. To explore N dynamics and potential mechanisms that modulate the mixing behaviors, we measured concentrations and natural isotopic compositions of multiple N species (nitrate: NO3 −, nitrite: NO2 −, ammonium: NH4 +, and particulate nitrogen) in a typical eutrophic estuary in southern China. Additionally, N uptake and oxidation rates were measured by using isotope labelling techniques to evaluate processes potentially offsetting the conservative mixing of specific N pools. We found that NO3 − followed conservative two end‐member mixing with dual isotopes varying in a narrow range (<1–2‰) due to low microbial preferences. Moreover, δ 15 N‐NO2 − revealed a nonconservative pattern with an involvement of multiple end‐members. The dominant N transformation processes shifted downstream. In the upper estuary, ammonia oxidation ( 20 μmol L −1 day −1 ) dominated NH4 + removal and was accompanied by NO2 − accumulation. In the middle‐lower estuary, NH4 + uptake became dominant, with phytoplankton showing strong preference for it over NO3 − and NO2 − . Based on measured NH4 + uptake rates (9.1–12.5 μmol L −1 day −1 in the light and 0.9 μmol L −1 day −1 in the dark), short water residence time (<1 day) was required to maintain the conservative mixing. Coupling N isotopes in multiple nitrogen species with measurements of N uptake and nitrification, we successfully uncovered N dynamics and distinguished biological processes from physical mixing. Key Points: Phytoplankton much prefer ammonium over nitrate and nitrite in eutrophic estuary Oxidation of ammonia was significantly higher than nitrite in turbid water δ 15 N‐NO2 – nicely reveals multiple nitrogen end‐members